The mussel filter–pump – present understanding, with a re‐examination of gill preparations. (1st December 2014) - Riisgård, Hans Ulrik; Funch, Peter; Larsen, Poul S.
Abstract Filter feeding in mussels is a secondary adaptation where the gills have become W‐shaped and greatly enlarged, acting as the mussel filter–pump. Water pumping and particle capture in the blue mussel, Mytilus edulis, have been studied over many years. Here, we give a short status of the present understanding of ciliary structure and function of the mussel filter–pump, supplemented with new photo‐microscope and scanning electron microscopy (SEM) pictures of gill preparations. Pumping rate (filtration) and pressure to maintain flow have been extensively studied so the power delivered by the mussel pump to the water flow is known (1.1% of total respiratory power), but the actual cost based on gill respiration is much higher (19%), implying that the cost of maintaining of the large gill pump is considerable and that only relatively little energy can be saved by stopping or reducing the activity of the water‐pumping cilia so that continuous feeding with a 'minimal scaled' pump is cheaper than discontinuous feeding with a correspondingly larger pump. According to the present view, the pump proper is the beating lateral cilia (lc) on the gill filaments and particle capture is accomplished by the action of laterofrontal cirri (lfc) transferring particles from the main water current to the frontal gill filament currents driven by frontal cilia (fc). Unexplained aspects include retention efficiency according to particle size and the role of pro‐laterofrontal cilia (p‐lfc) placed between the lfc and fc. The structure of cilia and the mode of ciliary beating have been re‐examined in this study by new high‐resolution light and scanning electron microscopy of isolated gill preparations exposed to serotonin (5‐HT) stimulation which can activate the lc and lfc at low concentrations (10−6 M), but removes the lfc from the interfilament canals at higher concentrations (10−5 M).